Pola Komunikasi Guru dan Murid dengan Autisme di SDIT Mutiara Hati Tambun Selatan: Studi Deskriptif tentang Komunikasi Interpersonal antara Guru dan Murid dengan Autisme di SDIT Mutiara Hati Tambun Selatan - Isma, Syafrina Nur; Tayo, Yanti; Teguh, Made Panji (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The research discussed in this journal focuses on the communication patterns of teachers and students with autism at SDIT Mutiara Hati Tambun Selatan. Students with autism are those who have an interaction impairment, have difficulty communicating with their surroundings, cannot look others in the eye, and prefer to withdraw into their own world. The objective of this study was (1) to explore interpersonal communication patterns between teachers and students with autism at SDIT Mutiara Hati Tambun Selatan. (2) Aims to learn the verbal or nonverbal communication used in the admission of autistic children at Mutiara Hati Tambun Selatan Integrated Islamic Primary School. (3) Exploring factors that support and hinder teaching and learning activities at Mutiara Hati Tambun Selatan Integrated Islamic Primary School. With qualitative descriptive research method. The theory used in this study is that Devito's five positive attitudes support interpersonal communication. The results of this study suggest that students with autism who attend regular private schools with other normal children report that interpersonal communication or interpersonal communication patterns are use is more likely in the form of verbal or oral communication with repetition (drill) and the use of slow intonation and soft language. During this time, nonverbal communication is used more in the form of movements interspersed with stories, or smiles, hand gestures, as a form of appreciation for the positive things that students have. autistic have done with the purpose that they have confidence in themselves to interact with their surroundings. keyword: communication pattern, interpersonal communication, verbal communication, nonverbal communication, students with autism